2D Marine Seismic data Analysis Using Comparison of Kirchhoff’s Migration Method and Finite Difference Method (Case Study: Nias Basin, North Sumatera) - Annisa, Cindy Fatika Nur; Muliadi, Muliadi; Ivansyah, Okto; Subarsyah, Subarsyah (JURNAL GEOCELEBES, 2024)
Seismic migration is one of the important stages in seismic data processing which aims to map seismic events to their actual positions. The migration process used in this study is post-stack time migration in the time domain using the Kirchhoff migration technique and the finite difference method to determine the results of subsurface imaging from the two migration techniques and then compare them to determine the accuracy of selecting the appropriate migration for the L08 basin trajectory research area. Nias basin, North Sumatra. The processing steps are carried out according to the preprocessing to processing stages in the Promax 5000 software. Based on the results of the study, the optimum use of aperture migration in Kirchhoff migration will produce good subsurface cross-sectional imaging. The aperture value used is 3000 ms. In the finite difference migration, subsurface imaging is much more focused with a time step variation of 10 ms, whose function is to focus the hyperbolic diffraction energy on the migration data.